Competitive Radical Migrations and Ribose Ring Cleavage in Adenosine and 2'-Deoxyadenosine Cation Radicals - Zima, Václav; Marek, Aleš; Tureček, František (The journal of physical chemistry. A, 2024)
We report a combined experimental and computational study of adenosine cation radicals that were protonated at adenine and furnished with a radical handle in the form of an acetoxyl radical, •CH2COO, that was attached to ribose 5'-O. Radicals were generated by collision-induced dissociation (CID) and characterized by tandem mass spectrometry and UV-vis photodissociation action spectroscopy. The acetoxyl radical was used to probe the kinetics of intramolecular hydrogen transfer from the ribose ring positions that were specifically labeled with deuterium at C1', C2', C3', C4', C5', and in the exchangeable hydroxyl groups. Hydrogen transfer was found to chiefly involve 3'-H with minor contributions by 5'-H and 2'-H, while 4'-H was nonreactive. The hydrogen transfer rates were affected by deuterium isotope effects. Hydrogen transfer triggered ribose ring cleavage by consecutive dissociations of the C4'-O and C1'-C2' bonds, resulting in expulsion of a C6H9O4 radical and forming a 9-formyladenine ion. Rice-Ramsperger-Kassel-Marcus (RRKM) and transition-state theory (TST) calculations of unimolecular constants were carried out using the effective CCSD(T)/6-311++G(3d,2p) and M06-2X/aug-cc-pVTZ potential energy surfaces for major isomerizations and dissociations. The kinetic analysis showed that hydrogen transfer to the acetoxyl radical was the rate-determining step, whereas the following ring-opening reactions in ribose radicals were fast. Using DFT-computed energies, a comparison was made between the thermochemistry of radical reactions in adenosine and 2'-deoxyadenosine cation radicals. The 2'-deoxyribose ring showed lower TS energies for both the rate-determining 3'-H transfer and ring cleavage reactions.
Keywords: Deuterium; Deoxyadenosines; vodík; ribosa; kationty; Adenosine; deoxyadenosiny; Kinetics; Cations; Ribose; Deoxyribose; Free Radicals; kinetika; volné radikály; deuterium; adenosin; Hydrogen; deoxyribosa